Perspektif laki-laki Bali mengenai perkawinan Nyentana - Sagung Kartika Veda Jayanti Putera; Intan Primadini (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
Balinese people who are unable to produce male offspring use Nyentana, a matrilineal mating system. In the midst of patriarchal culture and a dense patrilineal kinship system, it is difficult for men to perform Nyentana marriage. The study intends to discover how Balinese men perceive Nyentana marriage as a type of matrilineal marriage. This is an exploratory qualitative study with a phenomenological approach, and data was gathered through direct interviews with four Balinese men who had performed Nyentana marriages. The findings revealed that the concept of patriarchal society was used, which stated that men were dominant and women were subordinate. According to the participants in this study, there is no clear distinction between patrilineal marriages in general and Nyentana marriages in particular; men remain the head of the family and exercise leadership in the indigenous community system. Men who have participated in Nyentana Marriage believe that this matrilineal marriage is widespread, particularly in the Tabanan region. Some participants also mentioned that this type of marriage is not permitted in all areas of Bali. Men who have participated in Nyentana mating believe this is normal because men continue to dominate and are encouraged by the customary system. It can be concluded that men who have participated in Nyentana marriage see no distinction between Nyentana marriage as a type of matrilineal marriage and patrilineal marriage in general.